Effectiveness of CKD Exacerbation Countermeasures in Izumo City - Takafumi Ito (MDPI AG, 2021)
To diagnose chronic kidney disease (CKD) at an early stage, it is important to promote appropriate health guidance and consultation recommendations through regular medical examinations and implementation of continuous high-quality and appropriate treatment. From fiscal year (FY) 2018, Izumo City has initiated the “Izumo City CKD Exacerbation Countermeasures” program. In this study, we aimed to report on the methods undertaken and the effects of this program. Residents aged 40–74 years who underwent specific health checkups from the Izumo City National Health Insurance in FY2018 and FY2019 were included. The rates of CKD re-examination candidates, re-examinations implementation, nephrologist referrals, and health guidance referrals between FY2018 and FY2019 were compared. The rate of CKD re-examination candidates in both years remained unchanged at approximately 7%. The rate of re-examination implementation in FY2019 significantly increased relative to that in FY2018 (p < 0.001). Subsequent re-examination candidate trends showed that the rate of nephrologist referrals did not increase. However, the rate of city health guidance referrals significantly increased (p < 0.001). Increase in the re-examination and health guidance examination rates indicate improved awareness of CKD among the public and family doctors, and it is expected to prevent CKD exacerbation in the future.